UNDERSTANDING SPEECH ACTS: THE INTERSECTION OF LANGUAGE AND ACTION (Western European Journal of Modern Experiments and Scientific Methods, 2025)
Speech act theory, pioneered by philosophers like J.L. Austin and John Searle, offers profound insights into how language functions not just to convey information but to perform actions. This article explores the fundamental concepts of speech acts, categorized into locutionary, illocutionary, and perlocutionary acts. We examine their applications across various fields, the critiques of the theory, and the implications for understanding human communication. By delving into the intricacies of speech acts, we highlight their significance in both linguistic theory and everyday interactions.